“Dual awakening?” : Mindful social action in the light of the de-contextualization of Socially Engaged Buddhism - Zalta, Anja (Poligrafi, 2022)
The paper presents the concept of “dual awakening”, which is based on the Buddhist mindfulness appropriated by socially engaged Buddhism as a method to recognize and implement a “wholesome” paradigm on both the social and individual level. In the first half of the paper, I analyze the idea of “dual awakening” in the Southeast Asian context, especially in the case of the Sarvodaya Sramadana movement in Sri Lanka, In the second part of the paper, I review some of the research on (mindfulness) meditation in the West to critically evaluate the de-contextualization of transferring Buddhist ideas and methods (such as cultivating empathy and compassion as a basis for social action) into the Western modernist paradigm.